Morphological characterization of a pharmaceutical tablet coating bed using an artificial vision algorithm - Alpízar-Castillo, Joel Jesús (2021)
The pharmaceutical industry is constantly searching for methods to optimize its processes. In the present investigation was developed a vision system that allows to morphologically characterize the bed of pharmaceutical tablets during the coating process. As a result, an artificial vision algorithm was designed, which allows to quantify the tablets shown in the image and determine the area of each one, through the use of the Hough transformation and the Canny filter, based on a flat and static model of the coating bed of pharmaceutical tablets. An approximation of the angular position of the pharmaceutical tablets with respect to the optical axis of the camera was obtained, according to the number of layers of tablets in the coating bed.